2006
DOI: 10.1051/0004-6361:20064848
|View full text |Cite
|
Sign up to set email alerts
|

First direct detection of a Keplerian rotating disk around the Be star $\mathsf{\alpha}$ Arae using AMBER/VLTI

Abstract: Aims. We aim to study the geometry and kinematics of the disk around the Be star α Arae as a function of wavelength, especially across the Brγ emission line. The main purpose of this paper is to understand the nature of the disk rotation around Be stars. Methods. We use the AMBER/VLTI instrument operating in the K-band, which provides a gain by a factor of 5 in spatial resolution compared to previous MIDI/VLTI observations. Moreover, it is possible to combine the high angular resolution provided with the (medi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
135
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(158 citation statements)
references
References 37 publications
(43 reference statements)
18
135
0
5
Order By: Relevance
“…5.3 to explain this effect. We see that the differential phase plots exhibit "S" shapes, which are clear signatures for rotating disks (Meilland et al 2007b). The absence of this "S" shape for the B 2 baseline observation of 48 Per perhaps comes from the B 2 baseline being oriented close to the direction of the stellar rotational axis so that no photocenter displacement, which produces a fringe phase shift, is expected in this direction.…”
Section: Data In the Differential Analysis Modementioning
confidence: 78%
“…5.3 to explain this effect. We see that the differential phase plots exhibit "S" shapes, which are clear signatures for rotating disks (Meilland et al 2007b). The absence of this "S" shape for the B 2 baseline observation of 48 Per perhaps comes from the B 2 baseline being oriented close to the direction of the stellar rotational axis so that no photocenter displacement, which produces a fringe phase shift, is expected in this direction.…”
Section: Data In the Differential Analysis Modementioning
confidence: 78%
“…This observable has been intensively used to study the kinematic of circumstellar environments (e.g. Berio et al 1999;and Meilland et al 2007). In Figs.…”
Section: Structures At the Surfacementioning
confidence: 99%
“…From CHARA/VEGA measurement to be published in Mourard et al (2014). Stee et al 2012 or radiative transfer codes such as SIMECA (Meilland et al 2007a, Meilland et al 2007b, BEDSIK (Tycner et al 2011), or HDUST (Štefl et al 2009). In all cases the authors found that the circumstellar emission stems from a thin equatorial disk.…”
Section: Mass Loss and Circumstellar Environmentsmentioning
confidence: 99%